Evaluation of PMSG (Oodev®) application on hepatosomatic and gonadosomatic index of snakehead fish - Hutagalung, Rizal Akbar; Widodo, Maheno Sri; Faqih, Abdul Rahem (Indonesian Society of Scientific Aquaculture (ISSA), 2015)
ABSTRACT Snakehead fish (Channa striata) is a freshwater fish commodities that have high economic value, while their needs depend on natural catching. In general, hormonal induction commonly used for the efficiency of female parent utilization and enhancement quality and quantity of fish fry. One of the hormones that can be used is pregnant mare serum gonadotropin (PMSG) and antidopamine with trademark Oodev®. These hormones contain many elements follicle stimulating hormone (FSH) which can trigger the early stages of gonad maturity. The purpose of this research was to determine the effectiveness of hormone PMSG on gonadosomatic index (GSI) and hepatosomatic index (HSI). The size of female fish was 30−40 cm, weighing of 500−700 g, adapted in the aquarium and then induced with different doses of PMSG, namely: treatment A dose: 0.75 mL/kg; B: 1.0 mL/kg; C: 1.25 mL/kg; D: 1.5 mL/kg and be repeated three times. Fishes were then reared up to 72 hours to determine the development of GSI and HSI. The results showed that the best treatment was at dose of 1.25 mL/kg with GSI and HSI values of 1.37% and 3.35%, respectively. Keywords: PMSG, GSI, HSI, snakehead fish ABSTRAK Ikan gabus (Channa striata) merupakan salah satu komoditas air tawar yang mempunyai nilai ekonomi tinggi. Saat ini pemenuhan kebutuhan hanya bergantung pada hasil penangkapan dari alam. Pada umumnya cara pemijahan buatan dengan induksi hormon dilakukan untuk efisiensi penggunaan induk serta peningkatan kualitas dan kuantitas benih ikan. Salah satu hormon yang dapat digunakan adalah pregnant mare serum gonadotropin (PMSG) dan antidopamin dengan merk dagang Oodev®. Hormon-hormon tersebut banyak mengandung unsur follicle stimulating hormon (FSH) yang dapat memicu kematangan gonad tahap awal. Tujuan dari penelitian ini adalah untuk menguji efektivitas hormon PMSG terhadap nilai indeks gonadosomatik (IGS) dan indeks hepatosomatik (IHS). Induk ikan gabus yang digunakan berukuran 30−40 cm dengan bobot 500–700 g, diaklimatisasikan di akuarium kemudian diinduksi hormon PMSG dengan perlakuan dosis A: 0,75 mL/kg; B: 1,0 mL/kg; C: 1,25 mL/kg; D: 1,5 mL/kg dan dilakukan pengulangan sebanyak tiga kali. Selanjutnya ditunggu hingga 72 jam untuk mengevaluasi perkembangan IGS dan IHS nya. Hasil penelitian menunjukkan bahwa perlakuan terbaik adalah dosis 1,25 ml/kg dengan nilai rata-rata IHS 1,37% dan IGS 3,35%, Kata kunci: PMSG, IGS, IHS, ikan gabus